Bacterial isolates and antimicrobial susceptibility profiles of pediatric meningitis at comprehensive specialized hospitals in Bahir Dar, Northwest Ethiopia - Tadese Sisay; Daniel Mekonnen; Mitkie Wendmagegn; Ayenew Berhan; Addisu Melese (PLoS ONE, 2026)
Bacterial meningitis remains a major cause of morbidity and mortality among children in low-resource settings. Delayed diagnosis and antimicrobial resistance complicate effective management, and recent local data from Ethiopia are limited. This study aimed to determine the bacterial etiology and antimicrobial susceptibility patterns among children with suspected bacterial meningitis in Northwest Ethiopia. A hospital-based cross-sectional study was conducted from June 3 to December 25, 2024, among 189 pediatric patients aged 0–14 years who were clinically suspected of bacterial meningitis at two comprehensive specialized hospitals in Bahir Dar. Cerebrospinal fluid samples were collected aseptically and analyzed using standard cytological, biochemical, and microbiological methods. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disk diffusion method in accordance with CLSI M100 (34th edition, 2024) guidelines. Data were entered and analyzed using SPSS version 26, and descriptive statistics, including frequencies and 95% confidence intervals for bacterial prevalence, were computed. Of the 189 cerebrospinal fluid samples analyzed, 10/189 (5.3%) were culture positive. Gram-negative bacteria accounted for 6/10 (60%) of isolates. Escherichia coli and Staphylococcus aureus were the most frequently identified pathogens, each representing 3/10 (30%), followed by Klebsiella pneumoniae at 2/10 (20%). Most confirmed cases occurred in infants aged 1–12 months. Ceftriaxone and imipenem were fully susceptible in Staphylococcus aureus and Klebsiella pneumoniae , while resistance was highest to ampicillin in Escherichia coli (2/3, 66.7%) and to ciprofloxacin in Staphylococcus aureus (1/3, 33.3%). Multidrug resistance among bacterial isolates was uncommon, with MDR detected in a single Escherichia coli isolate (33.3%), while no MDR was observed in other pathogens. In conclusion, Gram-negative bacteria predominated among pediatric bacterial meningitis cases in Northwest Ethiopia. These findings highlight the need for ongoing surveillance, improved laboratory capacity, and evidence-based antimicrobial stewardship to guide empirical therapy and improve pediatric outcomes.